PENGARUH EDUKASI KESEHATAN MELALUI MEDIA FLYER TERHADAP PENGETAHUAN PASIEN PROLANIS MENGENAI DIABETIC FOOT CARE - Musyrifah, Nur Uyuni; Sudiyat, Rahmat (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background : First ranked with the highest number of Diabetes Miletus targets in the city of Bandung is Babakan Sari Community Health Center, amounting to 1,635 sufferers. The high incidence of DM can result in complications of diabetic foot ulcers and can be life threatening if there is no proper treatment. Purpose : To determine the effectiveness of health education through flyer on Prolanis patients' knowledge of diabetic foot care. Method : The design of this research is Quantitative with a Quasi Experimental method and development of the ADDIE media model. Research subjects were taken using a total sampling technique, totaling 31 diabetes mellitus prolanis patients at the Babakan Sari Community Health Center, carried out on May 18 2024. Data analysis used the Wilcoxon test. Results : The media developed through the ADDIE model is diabetic foot care flyer media. The average pretest knowledge score for prolanis patients is 55.42 in the low knowledge level category and the posttest is 93.10 in the high knowledge level category. The p value of respondents' information some time recently and after being given wellbeing instruction through flyer media was (p=0.000). Conclusion : There is an effectiveness of health education through flyer media on the knowledge of prolanis patients at Babakan Sari Health Center regarding diabetic foot care. Recommendation : This research about can be created considering other potential factors such as demeanor and behavior factors.